Isolation and identification of fungi from the droppings of some poultry and some detergents effect on some of them. - Al-Temimay, Israa A.; Hasan, Alaa M. (Iraqi Journal of Science, 2022)
In Baghdad governorate, samples of dried birds waste were obtained from poultry cages for investigate the of the presence of fungi. There was a high proportion of Candida spp., Rhodotorula spp. and filamentous fungi that obtained from the dry droppings. Al samples gave a positive results included 177 isolates, these isolates includes different Candida species 62 isolates (35.02%), Rhodotorula spp. 28 isolates (15.81%), and the following filamentous genera: Aspergillus spp. 50 isolates (28. 24%), (A. niger 20 isolate, A. flavus 18 isolate, A. fumigatus 12 isolate), Penicillium spp. 11 isolates (6.21%) and Mucor spp. 26 isolate (14.68%). The inhibitory effect of the used detergents (with concentration of 10-1 mg/ml.( was ranged from 35 mm using pert plus shampoo to 5 mm in Fine liquid dish washing, while some detergents had no effect on both Candida and Rhodotorula species.